Production of pigments by rhodotorula mucilaginosa - Lau, Wai Xian (Universiti Malaysia Sarawak (UNIMAS), 2015)
Rhodotorula yeast belongs to the family of Cryptococcaceae, a subfamily of Rhodotorulodeae. Rhodotorula produces major carotenoid pigments like carotene, torularhodin, and torulene. Carotenoids are important natural pigments. The concentration and type of carotenoids production by genus Rhodotorula is influenced by the species of microorganism, the constituents of medium and culture conditions. The aim of this study was to investigate the growth, the production of carotenoids produced by Rhodotorula mucilaginosa using sago hampas hydrolysate (SHH). Carotenoid assay was conducted to perform the qualitative determination. The highest biomass (9.6 gil), carotenoid concentration (8.1 mgll) and specific productivity (845.9 Jlglg.h) were scored by Rhodotorula mucilaginosa. The production of carotenoids was carried out for 96 hours at 27°C. The obtained result has proved and demonstrated the capacity of R. mucilaginosa to produce carotenoid.